CAREER GUIDANCE SERVICES IN PREPARING TUNAGRAHITA STUDENTS ENTERED THE WORLD OF WORK - Marini Rahmatina (PABKI (Perkumpulan Ahli Bimbingan dan Konseling Islam) Indonesia, 2018)
This paper describes the method used or the way school counselor in providing assistance to students to determine the choice of the appropriate working with children who have mental handicaped so being able to prepare for entry into the environment work. The child's mental handicaped was the son who experience barriers on intellectual property. Education that may lead students to develop skills so that students can do the Polytechnic things independently after graduation from school. SLB Negeri Pembina Yogyakarta has the training program been ISO-standard skills, so being able to be used as another example of SLB. Education skills given to mental retardation, in addition to functioning selective, educative, therapist and creative can also serve as a provision of his life. Career guidance has a very important role for the sustainability of future students not only mental retardation as a container that is in charge of connecting students to be able to plan the future but can also be referring to the success of the child's mental handicaped entered the world of work. There are several methods in order to make a career of students mental handicaped can be guided by the method in groups, field trips, career day, exercise work (internship), demonstrations, experiments, and curricular activities. While individually i.e. career counseling and home visit.